The Governmentality of Black Beauty Shame Discourse, Iconicity and Resistance - Tate, Shirley Anne (Palgrave Macmillan UK, 2018)
This book uses the experiences and conversations of Black British women as a lens to examine the impact of discourses surrounding Black beauty shame. Black beauty shame exists within racialized societies which situate white beauty as iconic, and as a result produce Black 'ugliness' as a counterpoint. At the same time, Black Nationalist discourses present Black-white 'mixed race' women as bodies out of place within the Black community. In the examples analysed within the book, women disidentify from both the iconicities of white beauty and the discourses of Black Nationalist darker-skinned beauty, negating both ideals. This demonstration of Foucaldian counter-conduct can be read as a form of disalienation from the governmentality of Black beauty shame. This fascinating volume will be of interest to students and scholars of Black identity, Black beauty and discourse analysis. Shirley Anne Tate is Professor of Race and Education in the Carnegie School of Education, Leeds Beckett University, UK. She is also a Visiting Professor and Research Fellow at the Institute for Reconciliation and Social Justice, South Africa, with links to many other institutions worldwide. Her research interests centre around Black beauty, identity, performativity and Black diaspora politics.